Nilai Moral dalam Buku Cerita Kuafu Zhui Ri - Mella Tria Indrastuti (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2022)
In developing reading skills teaching materials, it is necessary to have reading texts as support. These reading texts were chosen not only because of their vocabulary corresponds to the level of the teaching materials, but also because they are qualified reading texts. One of the criteria for a good reading text is that it contains moral values ​​such as folklore books. This study has several objectives to find out the moral values ​​contained in the story book Kuafu Zhui Ri namely: (1) contains the core form of Confucius' teachings of Ai ren, (2) shows the principles of implementing the teachings of Confucius of Xiaodi, (3) shows the stages of implementing the teachings of Confucius of Zhong and Shu. The data in this study are limited to Chinese sentences in stories that contain moral values. The entire data is classified based on the core form, the principle of implementation and the stages of implementing moral values ​​according to the teachings of Confucius. The findings in this study are that the folklore of Kuafu Zhui Ri contains the moral values ​​of Confucius' teachings, which consist of (1) loving others, (2) filial piety, and (3) loyalty and forgiveness. Based on the research findings, it is hoped that the Kuafu Zhui Ri folklore can be applied in the world of education and used as a reference or input by the UNJ Mandarin Language Education Study Program when choosing reading texts in the development of textbooks for reading skills.